2021
DOI: 10.1128/jvi.00906-21
|View full text |Cite
|
Sign up to set email alerts
|

Hemagglutinins of Avian Influenza Viruses Are Proteolytically Activated by TMPRSS2 in Human and Murine Airway Cells

Abstract: Cleavage of the influenza A virus (IAV) hemagglutinin (HA) by host proteases is indispensable for virus replication. Most IAVs possess a monobasic HA cleavage site cleaved by trypsin-like proteases. Previously, the transmembrane protease TMPRSS2 was shown to be essential for proteolytic activation of IAV HA subtypes H1, H2, H7 and H10 in mice. In contrast, additional proteases are involved in activation of certain H3 IAVs, indicating that HAs with monobasic cleavage site can differ in their sensitivity to host… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 70 publications
0
25
0
Order By: Relevance
“…Many proteases have been identified as likely candidates to cleave monobasic HA0 (reviewed in [ 131 ]). The Type II Transmembrane Serine Protease (TMPRSS2) has been shown to activate most, but not all, human and avian HAs in mice [ 133 , 134 , 135 , 136 , 137 ], human respiratory cell culture models [ 138 , 139 ], and overexpression systems [ 132 ]. Human Airway Trypsin (HAT) is expressed in respiratory ciliated cells and can cleave LPAIV HA0, albeit to a lesser extent than TMPRSS2 [ 132 ].…”
Section: Proteases That Activate Hamentioning
confidence: 99%
See 1 more Smart Citation
“…Many proteases have been identified as likely candidates to cleave monobasic HA0 (reviewed in [ 131 ]). The Type II Transmembrane Serine Protease (TMPRSS2) has been shown to activate most, but not all, human and avian HAs in mice [ 133 , 134 , 135 , 136 , 137 ], human respiratory cell culture models [ 138 , 139 ], and overexpression systems [ 132 ]. Human Airway Trypsin (HAT) is expressed in respiratory ciliated cells and can cleave LPAIV HA0, albeit to a lesser extent than TMPRSS2 [ 132 ].…”
Section: Proteases That Activate Hamentioning
confidence: 99%
“…Gotoh et al found that a blood clotting factor Xa-like protease from embryonated chicken eggs activates LPAIV HA [ 148 ]. Recently, it has been shown that mallard duck TMPRSS2 can cleave H1–12, H15, and H16, but not the H14 prototype that was used in the study [ 139 ]. The NA of a few specific viral strains can also mediate the non-canonical cleavage of HA0.…”
Section: Proteases That Activate Hamentioning
confidence: 99%
“…In order to acquire fusion competence, HA depends on proteolytic cleavage of a linker at the HA1-HA2 interface, a process that triggers conformational rearrangements and enables pH dependent exhibition of the viral fusion peptide [41]. TMPRSS2-mediated cleavage has been described mainly for influenza A viruses; in accordance with the substrate preference of the proteases, cleavage occurs preferentially after a monobasic motif in the linker region [42]. TMPRSS2 was identified as an HA-activating protease in 2006 when Böttcher and colleagues demonstrated TMPRSS2and HAT-(human airway trypsin-like protease, TMPRSS11D)dependent activation of human-pathogenic influenza strains H1N1, H2N9 and H3N2 [43].…”
Section: Influenza Virusmentioning
confidence: 99%
“…This form is incapable of autoproteolytic activation and lacks proteolytic activity. Consequently, treatment with T-ex5 hampered the replication of monobasic influenza virus strains and SARS-CoV-2 S activation in cell lines and primary cells [7,13,42,56]. In an in vitro screening approach, Chen and colleagues identified therapeutic compounds that reduce TMPRSS2 protein expression in the low-to sub-micromolar range.…”
Section: Inhibitors Of Tmprss2 Expressionmentioning
confidence: 99%
“…The exposed hydrophobic fusion peptide of S2 inserts into the target cell membrane and mediates membrane fusion to release the viral genome into the cytosol for transcription and replication ( Hoffmann et al, 2021b ; Zhang et al, 2020 ). TMPRSS2 plays important roles in the entry of respiratory viruses, such as SARS-CoV-2, SARS-CoV and Avian Influenza Viruses ( Bestle et al, 2021 ; Glowacka et al, 2011 ; Song et al, 2020 ). Inhibition of TMPRSS2 significantly prevents SARS-CoV and SARS-CoV-2 from entering into target cells ( Hoffmann et al, 2021b ; Kawase et al, 2012 ).…”
Section: Endocytosis-mediated Entry Of Sars-cov-2mentioning
confidence: 99%